Recognition of a Person’s Rights and Ethical Fulfilment - Brugiatelli, Vereno (European Journal of Multidisciplinary Studies, 2017)
Man's ethical fulfilment often faces objective obstacles in the deprivation of rights. The negation of the recognition of certain fundamental rights, or worse, the radical misrecognition of man, which translates into different forms of violence, often artfully disguised both on an individual and collective level, produces devastating consequences in the private life of a person upsetting all forms of positive self-esteem. The recognition of human qualities, accompanied by the right to express and extend them, is an integral part of the ethical life of each individual and, at the same time, constitutes a fundamental moment in the construction of a responsible civilized community. In this dissertation, I aim to analyse the connection between ethical life and human rights in order to draw attention to the repercussions that the recognition and misrecognition of liberty produce with regard to man's ethical fulfilment. From this perspective, I intend to highlight the importance of the existence of favourable juridical and institutional conditions to ensure ethical fulfilment. At this level, I will underline that the deprivation of capabilities is often the main cause of the profound sense of discontent affecting individuals in their desperate attempt to realise a type of existence which corresponds to their ambitions.
Keywords: recognition, misrecognition, right, capabilities.